How To Solve It : A New Aspect of Mathematical Method - Pólya, George (Princeton, N.J.: Princeton University Press, 1945)
This book stems from the author's attempt to understand not only the solution of a problem but also the motives and procedures of the solution, and trying to explain these motives and procedures to others.
Includes bibliographical references.
ne 22/02/2018
Loans
Keywords: Mathematics; Mathematical methods